Treatment Algorithm in Cancer-Associated Thrombosis: Updated Canadian Expert Consensus. - Carrier, Marc; Blais, Normand; Crowther, Mark; Kavan, Petr; Le Gal, Grégoire; Moodley, Otto; Shivakumar, Sudeep; Suryanarayan, Deepa; Tagalakis, Vicky; Cynthia Wu; Lee, Agnes Y. Y. (Current Oncology, 2021)
Patients with cancer-associated thrombosis (CAT) are at high risk of recurrent venous thromboembolism (VTE) and major bleeding complications. Risks vary significantly between individuals based on cancer status, treatment, and other characteristics. To facilitate the evidence-based management of anticoagulant therapy in this patient population, a committee of 11 Canadian clinical experts updated a consensus-based algorithm for the acute and extended treatment of symptomatic and incidental CAT that was developed in 2018. Following a systematic review of the literature, updates to the algorithm were discussed during an online teleconference, and the algorithm was subsequently refined based on feedback from committee members. Clinicians using this treatment algorithm should consider bleeding risk, type of cancer, and drug-drug interactions, as well as patient and clinician preferences, in tailoring anticoagulation for patients with CAT. Anticoagulant therapy should be adapted as the patient's cancer status and management change over time.